Middle to Late Miocene Age for the End of Amphibolite‐Facies Mylonitization of the Alpine Schist, New Zealand: Implications for Onset of Transpression Across the Alpine Fault. Issue 12 (18th December 2019) - Ring, Uwe; Glodny, Johannes; Angiboust, Samuel; Little, Tim; Lang, Karl A.
Abstract: We report five new Rb‐Sr muscovite‐based isochron ages, which are the first to constrain the timing of amphibolite‐facies mylonitization of the Alpine Schist in the Southern Alps of New Zealand. The ages range from 13.1 ± 4.3 to 8.9 ± 3.2 Ma (2 σ uncertainties) for mylonite directly above the Alpine Fault. The weighted mean age of 10.74 ± 0.57 Ma is within uncertainty of a published 40 Ar/ 39 Ar illite/mica upper‐intercept age of 11.5 ± 0.5 Ma measured at the same locality. The end of amphibolite‐facies mylonitization occurred at metamorphic conditions of 560–570 °C and 0.9–1.1 GPa as derived from pseudosection analysis in the NCTiKFMASH system. We interpret Miocene metamorphism to reflect transpressional crustal thickening and formation of a thick crustal root supporting early Southern Alps topography at or prior to 10.74 ± 0.57 Ma. Additional 2–1 Ma Rb‐Sr biotite, 40 Ar/ 39 Ar muscovite, and 40 Ar/ 39 Ar biotite ages reflect isotopic closure during rapid cooling along the Alpine Fault in the Pleistocene. The Miocene mylonitization ages and the Pleistocene cooling ages define a distinct two‐stage cooling and exhumation history for the Alpine Schist with initial cooling of 10 °C/Myr and exhumation rates of 2–4 km/Myr. Final cooling since 2 Ma was >100 °C/Myr at exhumation rates of 5–6 km/Myr. We interpret the two‐phase cooling history by movement of the mylonite through a strongly nonlinear thermal structure. An older 60.5 ± 0.7 Ma metamorphic event is also preserved as a Rb‐Sr crystallization age of a predeformational muscovite‐plagioclase assemblage in a sheared pegmatite. Key Points: We present the first quantitative data constraining the timing of Cenozoic Alpine Schistmylonitization and metamorphism We present evidence for middle Miocene crustal thickening in the Southern Alps of New Zealand The Alpine Schist has a distinct two‐phase cooling history